Safety Aspects of Stationary Battery Energy Storage Systems - Minglong He; Daniel Chartouni; Daniel Landmann; Silvio Colombi (Batteries)
Stationary battery energy storage systems (BESS) have been developed for a variety of uses, facilitating the integration of renewables and the energy transition. Over the last decade, the installed base of BESSs has grown considerably, following an increasing trend in the number of BESS failure incidents. An in-depth analysis of these incidents provides valuable lessons for improving the safety of BESS. This paper discusses multiple safety layers at the cell, module, and rack levels to elucidate the mechanisms of battery thermal runaway and BESS failures. We further provide insights into different safety aspects of BESS, covering the system architecture, system consideration, safety standards, typical quality issues, failure statistics, and root causes. Various mitigation strategies are recommended and summarized. We highlight the importance of multi-disciplinary approaches in knowing, managing, and mitigating the risks associated with BESS. In general, this review paper serves as a guide for understanding the safety of BESS.